El derecho constitucional a la presunción de inocencia y la prisión preventiva en la ciudad de Machala en los años 2011-2012. - Rivera Romero, Sara Viviana (2013)
This research work aims to explain a legal issue regarding the application of a deprivation of liberty, and if that application violent a constitutional principle as the presumption of innocence, which is a basic principle of due process and that is a right human recognized by our constitutional and legal establishment. So manifest that criminal procedural practice in Ecuador, said that sought in the application of preventive detention, without considering that it is a personal injunction exceptional and that dictates when other alternatives to these are impossible for processing appear at the trial stage, but this measure of preventive detention should be issued subject to criminal constitutional and procedural rules. Therefore in this paper we was necessary to analyze issues such as concept, objectives, requirements, legal nature, according to what has our constitution, the code of criminal procedure, and what it tells us jurisprudence, national and international doctrine, existed, exist and will exist always part of the primary and dominant society interest that the investigation of crimes is made subject to due process and respect for human rights, this means of course without violating the principles of due process of procedural subjects and this in order to ensure the rule of criminal law and its correct and proper application.